Instagram Translation Machine: Does It Help Arabic Students to Know Arabic-Indonesian Translation Well? - Ulfa Febriyanti; Tsara Aliya Salsabila (IAIN Salatiga, 2022)
In recent decades, Instagram has launched a translation feature to help its user understand the caption in every Instagram posts. Its presence also has an impact on its users, including Arabic students. The purpose of this study is to identify the students’ perceptions about the use of these features and to know its impact on their understanding. The data collection technique was carried out in two different stages using a screening model. We distributed questionnaires to 24 Arabic students at Indonesia University of Education to find out the students' experiences while using this feature. The findings show that this feature is convenient, and the translations are quite understandable, but it is not uncommon for them to find translations that do not fit the context because this feature can produce good translations if the source language use the standard language. Most of the students also admitted that this feature affected their insight about translation. It can be used as an interesting learning media to be more creative and increase their motivation and interest in learning Arabic language in daily lives.